A microcrystalline composite glass optical fiber with broadband yellow light emission and a preparation method thereof

By using microcrystalline composite glass fiber with NaLa(WO4)2:Dy3+ microcrystalline glass fiber core, the shortcomings of existing Dy3+ doped fluoride glass fiber in yellow laser output performance are solved, and broadband and strong yellow light emission are achieved, suitable for direct output of tunable or ultrafast yellow lasers.

CN116589196BActive Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310470993.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-04-04
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The existing Dy3+ doped fluoride glass fibers have shortcomings in the output performance of yellow light lasers, including poor chemical stability, low laser damage threshold, low fluorescence branches and low emission cross-section, which limits the output power and tunability of yellow light lasers.

Method used

NaLa(WO4)2:Dy3+ microcrystalline glass is used as the core material, and the composite fiber is melted and fed through the core and heat treatment is performed to prepare a microcrystalline composite glass fiber with broadband yellow light emission. This method combines the non-uniform broadening spectral characteristics of NaLa(WO4)2 microcrystals with the flexibility of the fiber and the low laser threshold to achieve broadband and strong yellow light emission.

Benefits of technology

A broadband yellow light emission is realized, the half-height width of the emission peak can reach 18~22nm, maintaining a low transmission loss, providing a stable gain medium, suitable for direct output of tunable or ultrafast yellow light lasers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116589196B_ABST
    Figure CN116589196B_ABST
Patent Text Reader

Abstract

The invention discloses a microcrystalline composite glass optical fiber with broadband yellow light emission and a preparation method thereof; the cladding of the microcrystalline composite glass optical fiber is quartz glass, and the core is Dy 3+ Doped NaLa(WO4)2 microcrystalline glass. The present invention firstly pickles and dries the quartz glass tube, and then seals one end of the tube by taper drawing; places the core ceramic rod in the quartz glass tube to obtain an optical fiber preform; draws the optical fiber preform at a high temperature of 1950-2010°C to obtain an optical fiber precursor; and heat treats the optical fiber precursor at a temperature of 900-1000°C for 3-6h to obtain a microcrystalline composite glass optical fiber with broadband yellow light emission. The microcrystalline composite glass optical fiber prepared by the present invention has broadband and strong yellow light emission, and maintains low transmission loss, which can be Dy 3+ Doped yellow fiber lasers provide broadband luminescence and stable gain media, which are expected to achieve tunable or ultrafast yellow laser direct output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optical fibers, and in particular relates to a microcrystalline composite glass optical fiber emitting broadband yellow light and a preparation method thereof. Background Art

[0002] Visible yellow lasers with a wavelength range of about 565-590nm are widely used in laser medicine, laser radar, astronomical observation, etc. For example, in the biomedical field, hemoglobin has a high absorption rate for yellow lasers with a wavelength of 577nm, so there is an urgent need for yellow lasers in the treatment of skin diseases, vascular diseases and ophthalmic diseases. However, the output of yellow lasers is relatively difficult, and is currently mainly based on dye lasers and nonlinear frequency conversion, including sum frequency, frequency doubling and Raman shift. Dye lasers have high maintenance costs and low safety in use; while systems using nonlinear crystals and self-space alignment are complex, non-compact in structure, not conducive to integration, and have low pumping efficiency. In contrast, the use of laser diodes (LDs) to pump rare earth-doped optical fiber materials can directly realize yellow light transport, and yellow lasers can be output after resonant cavity mode selection and amplification. This direct emission method can eliminate complex nonlinear optical processes and has the advantages of simple system, low loss and high reliability. Based on trivalent Dy 3+ correspond 4 F 9 / 2 → 6 H 13 / 2 The transition of Dy has the strongest yellow emission near 570nm. The fluorescence branch of yellow light is relatively large, and there are multiple shorter wavelengths in the range from ultraviolet band to blue light band that can be used to directly excite ground state particles. 3+ It is considered to be the best rare earth ion for direct emission of yellow lasers. The main reason is that Dy 3+ The 4f transition in the visible range is spin-forbidden (resulting in relatively small blue light absorption cross sections and yellow light emission cross sections), and Dy 3+ The energy level structure is complex and cross relaxation is prone to occur, resulting in a low quenching threshold.

[0003] Traditional yellow laser crystals, such as Dy:YAG and Dy:ZnWO4, have good thermal conductivity and high mechanical strength, but their narrow yellow light emission spectrum (FWHM < 7nm) limits their application in pulsed lasers. 3+ The mainstream gain fiber used in doped fiber lasers is still fluoride glass fiber (Limpert.J, Zellmer H, Riedel P, et al. Laser oscillation in yellow and blue spectral rangein Dy 3+:ZBLAN[J].Electronics Lettres,2000,36(16):1386-1387;Fujimoto Y,Ishii O,Yamazaki M.575nm laser oscillation in Dy 3+ -doped waterproof fluoro-aluminateglass fiber pumped by violet GaN laser diodes[J].Solid State Lasers XX:Technology and Devices,2011,7912:79120J;Wang HJ,Zou JH,Dong CC,et al.High-efficiency,yellow-light Dy 3+ -doped fiber laser with tuning from568.7to 581.9nm[J].Optics Letters,2019,44(17):4423-4426; Luo SY,Gu H,Tang X,et al.High-power yellow DSR wavelength pulses generated from a mode-locked Dy:ZBLANfiber laser[J].Optics Letters,2022,47(5):1157-1160.). Although the above reports confirmed that Dy 3+ Doped fluoride glass fiber is used in continuous, tunable and pulsed yellow light lasers, but fluoride glass fiber still has many shortcomings. On the one hand, fluoride glass has relatively poor chemical stability and low laser damage threshold, which greatly limits the application of Dy 3+ The output power of the doped yellow fiber laser is improved; on the other hand, the fluoride ion radius in the fluoride glass is small, the polarizability is low, and the covalency to the surrounding local field is small, resulting in Dy 3+ The Ω2 value of Dy is small, and the fluorescence branching in the yellow light band is relatively low, which leads to a low emission cross section of yellow light emission and poor theoretical gain performance. 3+ Doped with other gain fibers to emit yellow light (Tian SH, Lun YP, Sun YS, et al. Silicate-clad Dy 3+doped multi-component phosphate glass core glass fiber for yellow laser applications [J]. Journal of Non-Crystalline Solids, 2022, 577, 121313.) and yellow laser output (Majewski MR, Jackson SD. Diode pumped silicate fiber for yellow laser emission [J]. OSA Continuum, 2021, 4 (11), 2845-2851.), but there has been no breakthrough in Dy 3+ Progress in yellow laser output performance of fluoride-doped glass fibers.

[0004] Therefore, to further improve the output performance of tunable or pulsed yellow laser, the key is not only to improve the Dy 3+ In order to solve the inherent yellow light emission problem, we need to develop a gain medium with broadband emission, stable chemical properties and high damage threshold. NaLa(WO4)2 crystal is composed of layered [WO4] tetrahedrons, and Na and La are randomly distributed at the corresponding lattice positions in a 1:1 ratio between layers, resulting in a disordered structure of the crystal and non-uniform broadening of the spectrum. In addition, NaLa(WO4)2:Dy 3+ The crystal has excellent yellow light gain performance (Wei YP,Tu CY,Wang HY,et al.Optical spectroscopy of NaLa(WO4)2:Dy 3+ single crystal[J].Journal of Alloys and Compounds,2007,438(1-2):310-316.), has great potential in realizing tunable or pulsed yellow laser output. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a broadband yellow light emitting microcrystalline composite glass optical fiber and a preparation method thereof. 3+ The characteristics of the crystal's non-uniform spectrum broadening and the advantages of the optical fiber's good flexibility and low laser threshold are used to prepare a microcrystalline composite glass optical fiber with broadband yellow light emission. The present invention uses the core melting method to draw the composite optical fiber, and then heat treats it to obtain NaLa(WO4)2:Dy with a controllable degree of crystallization. 3+Microcrystalline glass composite optical fiber. This method has wide applicability, and combined with the advantages of NaLa(WO4)2 microcrystals inhomogeneously broadening the spectrum, the microcrystalline composite glass optical fiber has broadband and strong yellow light emission, and maintains low transmission loss, which can be used for Dy 3+ Doped yellow fiber lasers provide broadband luminescence and stable gain media, which are expected to achieve tunable or ultrafast yellow laser direct output.

[0006] The half-width of the emission peak of the optical fiber of the present invention at 575 nm can reach 18 to 22 nm.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] A broadband yellow light emitting microcrystalline composite glass optical fiber, whose cladding is quartz glass and the core is Dy 3+ Doped NaLa(WO4)2 glass-ceramics.

[0009] Preferably, the Dy 3+ The chemical formula of doped NaLa(WO4)2 glass-ceramics is NaLa (1-x) (WO4)2:xDy 3+ , x = 0.03-0.07;

[0010] Further preferably, x=0.03, 0.04, 0.05, 0.06, 0.07.

[0011] Preferably, the core diameter of the microcrystalline composite glass optical fiber is 5 to 20 μm, and the outer diameter of the cladding is 120 to 130 μm.

[0012] Preferably, the microcrystalline composite glass optical fiber obtains broadband yellow light emission of 18 to 22 nm under the pumping of a blue light semiconductor laser.

[0013] Preferably, the precursor of the fiber core is a fiber core ceramic rod; and the method for preparing the fiber core ceramic rod comprises the following steps:

[0014] (a) mixing sodium carbonate powder, tungsten oxide powder, lanthanum oxide powder and dysprosium oxide powder, grinding and sintering;

[0015] (b) grinding the powder sintered in step (a), adding a binder to press into shape, sintering, and grinding into a cylinder to obtain a fiber core ceramic rod.

[0016] Further preferably, the purity of the sodium carbonate powder in step (a) is ≥99.9%, the purity of the tungsten oxide powder is ≥99.99%, the purity of the lanthanum oxide powder is ≥99.99%, and the purity of the dysprosium oxide powder is ≥99.99%;

[0017] Further preferably, the molar ratio of the sodium carbonate powder, tungsten oxide powder, lanthanum oxide powder and dysprosium oxide powder in step (a) is 1:4:0.93-0.97:0.03-0.07.

[0018] Further preferably, the sintering temperature in step (a) is 1000-1200° C. and the time is 6-10 hours; and the sintering is carried out in a muffle furnace.

[0019] Further preferably, the binder in step (b) is a PVA binder, and its mass percentage is 0.1-1.5% of the sintered powder; the sintering temperature is 1000-1200°C, and the time is 6-10h; and the sintering is carried out in a muffle furnace.

[0020] More preferably, the mass percentage of the binder is 0.5% of the sintered powder.

[0021] The method for preparing the above-mentioned microcrystalline composite glass optical fiber with broadband yellow light emission comprises the following steps:

[0022] (1) First, the quartz glass tube is pickled and dried, and then one end is sealed by taper;

[0023] (2) placing a fiber core ceramic rod in a quartz glass tube to obtain an optical fiber preform;

[0024] (3) Drawing the optical fiber preform at a high temperature of 1950-2010° C. to obtain an optical fiber precursor;

[0025] (4) heat treating the optical fiber precursor at 900-1000° C. for 3-6 hours to obtain a microcrystalline composite glass optical fiber emitting broadband yellow light.

[0026] Preferably, the wire drawing in step (3) is carried out in a high-temperature graphite furnace of Rasta;

[0027] Preferably, the heat treatment in step (4) is carried out in a muffle furnace.

[0028] Due to the adoption of the above technical solution, the present invention has the following positive effects and outstanding features compared with the prior art:

[0029] (1) The present invention is a broadband yellow light emitting microcrystalline composite glass optical fiber, which fully combines NaLa(WO4)2:Dy 3 + The characteristics of non-uniform spectrum broadening of microcrystalline glass and the good flexibility and low laser threshold of optical fiber make the microcrystalline composite glass optical fiber have broadband and strong yellow light emission. By controlling the crystallization degree and size of microcrystals, its broadband luminescence performance is outstanding, which is different from the common Dy 3+ The comparison of doped crystals is as follows:

[0030]

[0031]

[0032] (2) The present invention is a microcrystalline composite glass optical fiber with broadband yellow light emission. Through material design, the cladding is quartz glass and has good compatibility with existing optical fiber systems.

[0033] (3) The present invention provides a method for preparing a broadband yellow light emitting microcrystalline composite glass optical fiber. The preform preparation process has wide applicability and low cost. The core ceramic rod components can be adjusted according to application requirements. The drawing process is mature and can be drawn using a commercial drawing tower.

[0034] (4) The present invention provides a method for preparing a microcrystalline composite glass optical fiber with broadband yellow light emission. A composite optical fiber precursor is prepared based on a core melt drawing method, and then the composite optical fiber is heat treated to obtain a microcrystalline glass composite optical fiber with a controllable degree of crystallization, and the optical fiber maintains a low transmission loss.

[0035] (5) The broadband yellow light emitting microcrystalline composite glass optical fiber of the present invention can be used in yellow light fiber lasers, especially in tunable or ultrafast yellow light fiber lasers. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is an excitation spectrum diagram of the microcrystalline composite glass optical fiber with broadband yellow light emission prepared in Example 1 of the present invention.

[0037] Figure 2 This is a visible emission spectrum of the broadband yellow light emitting microcrystalline composite glass optical fiber prepared in Example 3 of the present invention under the excitation of a blue light semiconductor laser.

[0038] Figure 3 This is a transmission electron microscope image of the microcrystalline composite glass optical fiber with broadband yellow light emission prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but is not intended to limit the scope of protection thereof.

[0040] The quartz glass tube used in the embodiment is processed as follows: firstly, it is pickled and dried, and then one end is sealed by taper.

[0041] Example 1

[0042] Sodium carbonate powder (purity ≥ 99.9%) with a stoichiometric ratio of 1, tungsten oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 4, lanthanum oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.93 and dysprosium oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.07 were placed in a mortar and ground thoroughly, and then the mixed powder was sintered in a muffle furnace at 1100°C for 8 hours; the pure phase NaLa(WO4)2:Dy 3+ The sample was re-ground and 0.5% (relative to pure phase NaLa(WO4)2:Dy 3+ The sample) was placed in a mold and pressed into a strip block. The pressed sample was sintered in a muffle furnace at 1150°C for 6 hours. The sintered strip ceramic rod was then ground into a cylinder with a diameter of 3.8 mm and a length of 6 cm. The core ceramic rod was placed in a quartz glass tube with an inner diameter of 4 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform. The preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 1980°C, which is higher than the melting point of the core material. The core diameter of the optical fiber was 10 μm and the outer diameter of the cladding was 125 μm. Finally, the NaLa(WO4)2:Dy 3+ The crystal derived optical fiber was heat treated in a muffle furnace at 900°C for 4 h to obtain NaLa(WO4)2:Dy 3+ Microcrystalline composite glass optical fiber.

[0043] The excitation spectrum of microcrystalline composite glass fiber was tested by Edinburgh spectrometer FLS920. The emission spectrum of microcrystalline composite glass fiber was tested by OceanMaya2000 Pro fiber spectrometer, and the excitation source was 450nm semiconductor laser. The microstructure of nanocrystals in microcrystalline composite glass fiber was observed by FEI Talos F200x transmission electron microscope.

[0044] The excitation spectrum of the broadband yellow light emitting microcrystalline composite glass optical fiber prepared in Example 1 is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the half-width of the excitation peak of the optical fiber in the blue light band can reach 7 nm, which shows that the optical fiber of the present invention can be well matched with the commercial 450nm pump source and is conducive to improving the pump absorption efficiency, thereby helping to achieve tunable or ultrafast yellow light laser direct output.

[0045] Example 2

[0046] Sodium carbonate powder (purity ≥ 99.9%) with a stoichiometric ratio of 1, tungsten oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 4, lanthanum oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.94 and dysprosium oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.06 were placed in a mortar and ground thoroughly, and then the mixed powder was sintered in a muffle furnace at 1100°C for 10 hours; the pure phase NaLa(WO4)2:Dy 3+ The sample was re-ground and 0.5% (relative to pure phase NaLa(WO4)2:Dy 3+ The sample) was placed in a mold and pressed into a strip block. The pressed sample was sintered in a muffle furnace at 1050°C for 8 hours. The sintered strip ceramic rod was then ground into a cylinder with a diameter of 3.8 mm and a length of 6 cm. The core ceramic rod was placed in a quartz glass tube with an inner diameter of 4 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform. The preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2000°C, which is higher than the melting point of the core material. The core diameter of the optical fiber was 15 μm and the outer diameter of the cladding was 130 μm. Finally, the NaLa(WO4)2:Dy 3+ The crystal derived optical fiber was heat treated in a muffle furnace at 950°C for 3 h to obtain NaLa(WO4)2:Dy 3+ Microcrystalline composite glass optical fiber.

[0047] The excitation spectrum of microcrystalline composite glass fiber was tested by Edinburgh spectrometer FLS920. The emission spectrum of microcrystalline composite glass fiber was tested by OceanMaya2000 Pro fiber spectrometer, and the excitation source was 450nm semiconductor laser. The microstructure of nanocrystals in microcrystalline composite glass fiber was observed by FEI Talos F200x transmission electron microscope.

[0048] Example 3

[0049] Sodium carbonate powder (purity ≥ 99.9%) with a stoichiometric ratio of 1, tungsten oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 4, lanthanum oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.95 and dysprosium oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.05 were placed in a mortar and ground thoroughly, and then the mixed powder was sintered in a muffle furnace at 1100°C for 7 hours; the pure phase NaLa(WO4)2:Dy 3+ The sample was re-ground and 0.5% (relative to pure phase NaLa(WO4)2:Dy 3+The sample) was placed in a mold and pressed into a strip block. The pressed sample was sintered in a muffle furnace at 1100°C for 9 hours. The sintered strip ceramic rod was then ground into a cylinder with a diameter of 3.8 mm and a length of 8 cm. The core ceramic rod was placed in a quartz glass tube with an inner diameter of 4 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform. The preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2010°C, which is higher than the melting point of the core material. The core diameter of the optical fiber is 8 μm and the outer diameter of the cladding is 125 μm. Finally, the NaLa(WO4)2:Dy 3+ The crystal derived optical fiber was heat treated in a muffle furnace at 980°C for 4 h to obtain NaLa(WO4)2:Dy 3+ Microcrystalline composite glass optical fiber.

[0050] The excitation spectrum of microcrystalline composite glass fiber was tested by Edinburgh spectrometer FLS920. The emission spectrum of microcrystalline composite glass fiber was tested by OceanMaya2000 Pro fiber spectrometer, and the excitation source was 450nm semiconductor laser. The microstructure of nanocrystals in microcrystalline composite glass fiber was observed by FEI Talos F200x transmission electron microscope.

[0051] The visible emission spectrum of the broadband yellow light emitting microcrystalline composite glass optical fiber prepared in Example 3 under the excitation of a blue light semiconductor laser is shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the half-width of the luminescence peak of this optical fiber at 575nm can reach 20nm, which is more common in Dy 3+ The broadband luminescence performance of the doped crystal is outstanding, which is conducive to the direct output of tunable or ultrafast yellow laser.

[0052] Example 4

[0053] Sodium carbonate powder (purity ≥ 99.9%) with a stoichiometric ratio of 1, tungsten oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 4, lanthanum oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.96 and dysprosium oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.04 were placed in a mortar and ground thoroughly, and then the mixed powder was sintered in a muffle furnace at 1200°C for 6 hours; the pure phase NaLa(WO4)2:Dy 3+ The sample was re-ground and 0.5% (relative to pure phase NaLa(WO4)2:Dy 3+The sample) was placed in a mold and pressed into a strip block. The pressed sample was sintered in a muffle furnace at 1000°C for 10 hours. The sintered strip ceramic rod was then ground into a cylinder with a diameter of 3.8 mm and a length of 6 cm. The core ceramic rod was placed in a quartz glass tube with an inner diameter of 4 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform. The preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 1990°C, which is higher than the melting point of the core material. The core diameter of the optical fiber is 5 μm and the outer diameter of the cladding is 120 μm. Finally, the NaLa(WO4)2:Dy 3+ The crystal derived optical fiber was heat treated in a muffle furnace at 960°C for 6 h to obtain NaLa(WO4)2:Dy 3+ Microcrystalline composite glass optical fiber.

[0054] The excitation spectrum of microcrystalline composite glass fiber was tested by Edinburgh spectrometer FLS920. The emission spectrum of microcrystalline composite glass fiber was tested by OceanMaya2000 Pro fiber spectrometer, and the excitation source was 450nm semiconductor laser. The microstructure of nanocrystals in microcrystalline composite glass fiber was observed by FEI Talos F200x transmission electron microscope.

[0055] The transmission electron microscope image of the broadband yellow light emitting microcrystalline composite glass optical fiber prepared in Example 4 is as follows: Figure 3 As shown, Figure 3 The a in the figure indicates that the crystals precipitated in the microcrystalline glass fiber are nanocrystals with a diameter of 4 to 6 nm. Figure 3 The b in the figure is a high-resolution lattice fringe image, which shows that NaLa(WO4)2:Dy 3+ Nanocrystals will not cause significant scattering losses, allowing the optical fiber to maintain low transmission losses, which is conducive to the direct output of tunable or ultrafast yellow light lasers.

[0056] Example 5

[0057] Sodium carbonate powder (purity ≥ 99.9%) with a stoichiometric ratio of 1, tungsten oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 4, lanthanum oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.97 and dysprosium oxide powder (purity ≥ 99.99%) with a stoichiometric ratio of 0.03 were placed in a mortar and ground thoroughly, and then the mixed powder was sintered in a muffle furnace at 1000°C for 9 hours; the pure phase NaLa(WO4)2:Dy 3+ The sample was re-ground and 0.5% (relative to pure phase NaLa(WO4)2:Dy 3+The sample) was placed in a mold and pressed into a strip block. The pressed sample was sintered in a muffle furnace at 1200°C for 9 hours. The sintered strip ceramic rod was then ground into a cylinder with a diameter of 3.8 mm and a length of 8 cm. The core ceramic rod was placed in a quartz glass tube with an inner diameter of 4 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform. The preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2000°C, which is higher than the melting point of the core material. The core diameter of the optical fiber is 13 μm and the outer diameter of the cladding is 127 μm. Finally, the NaLa(WO4)2:Dy 3+ The crystal derived optical fiber was heat treated in a muffle furnace at 1000°C for 3 h to obtain NaLa(WO4)2:Dy 3+ Microcrystalline composite glass optical fiber.

[0058] The excitation spectrum of microcrystalline composite glass fiber was tested by Edinburgh spectrometer FLS920. The emission spectrum of microcrystalline composite glass fiber was tested by OceanMaya2000 Pro fiber spectrometer, and the excitation source was 450nm semiconductor laser. The microstructure of nanocrystals in microcrystalline composite glass fiber was observed by FEI Talos F200x transmission electron microscope.

[0059] The above embodiments are preferred implementation methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A microcrystalline composite glass optical fiber with broadband yellow light emission, characterized in that: Its cladding is quartz glass and its core is Dy 3 + Doped NaLa(WO4)2 glass-ceramics.

2. The microcrystalline composite glass optical fiber with broadband yellow light emission according to claim 1, characterized in that: The Dy 3+ The chemical formula of doped NaLa(WO4)2 glass-ceramics is NaLa (1-x) (WO4)2:xDy 3+ , x=0.03~0.

07.

3. The broadband yellow light emitting microcrystalline composite glass optical fiber according to claim 1, characterized in that: The core diameter of the microcrystalline composite glass optical fiber is 5-20 μm, and the outer diameter of the cladding is 120-130 μm.

4. The microcrystalline composite glass optical fiber with broadband yellow light emission according to claim 1, characterized in that: The microcrystalline composite glass optical fiber obtains 18-22nm broadband yellow light emission under the pumping of a blue light semiconductor laser.

5. The broadband yellow light emitting microcrystalline composite glass optical fiber according to claim 1, characterized in that: The precursor of the fiber core is a fiber core ceramic rod; the preparation method of the fiber core ceramic rod comprises the following steps: (a) mixing sodium carbonate powder, tungsten oxide powder, lanthanum oxide powder and dysprosium oxide powder, grinding and sintering; (b) grinding the powder sintered in step (a), adding a binder to press into shape, sintering, and grinding into a cylinder to obtain a fiber core ceramic rod.

6. The microcrystalline composite glass optical fiber with broadband yellow light emission according to claim 5, characterized in that: The purity of the sodium carbonate powder in step (a) is ≥99.9%, the purity of the tungsten oxide powder is ≥99.99%, the purity of the lanthanum oxide powder is ≥99.99%, and the purity of the dysprosium oxide powder is ≥99.99%; The amount ratio of the sodium carbonate powder, tungsten oxide powder, lanthanum oxide powder and dysprosium oxide powder is 1:4: 0.93-0.97: 0.03-0.

07.

7. The microcrystalline composite glass optical fiber with broadband yellow light emission according to claim 5, characterized in that: The sintering temperature in step (a) is 1000-1200° C. and the sintering time is 6-10 hours; the sintering is carried out in a muffle furnace.

8. The microcrystalline composite glass optical fiber with broadband yellow light emission according to claim 5, characterized in that: The binder in step (b) is a PVA binder, and its mass percentage is 0.1-1.5% of the powder after sintering; the sintering temperature is 1000-1200° C., and the time is 6-10 hours; and the sintering is carried out in a muffle furnace.

9. The method for preparing a microcrystalline composite glass optical fiber with broadband yellow light emission according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) First, the quartz glass tube is pickled and dried, and then one end is sealed by taper; (2) placing a fiber core ceramic rod in a quartz glass tube to obtain an optical fiber preform; (3) Drawing the optical fiber preform at a high temperature of 1950-2010° C. to obtain an optical fiber precursor; (4) heat treating the optical fiber precursor at 900-1000° C. for 3-6 hours to obtain a microcrystalline composite glass optical fiber emitting broadband yellow light.

10. The preparation method according to claim 9, characterized in that: The wire drawing in step (3) is carried out in a high temperature graphite furnace of Rasta; The heat treatment in step (4) is carried out in a muffle furnace.

Citation Information

Patent Citations

  • Low-loss high-strength all-glass optical fiber in 2 to 5 micron wave band and preparation method thereof

    CN109574509A

  • Dy&lt;3+&gt;-doped phosphate glass for outputting yellow laser, optical fiber and preparation method of Dy&lt;3+&gt;-doped phosphate glass

    CN113087388A